2007
DOI: 10.1007/s11094-007-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activity and clinical effects of trecrezan and other tris-(2-hydroxyethyl)ammonium salts of arylheteroacetic acids (A review)

Abstract: The results of an experimental and clinical study on the pharmacological properties of new compounds representing tris-(2-hydroxyethyl)ammonium salts (TES) of arylheteroacetic acids -in particular, tris-(2-hydroxyethyl)ammonium-2-methylphenoxyacetate (trecrezan) -are summarized. Trecrezan exhibits a modulating action on immunity and hemopoiesis and offers a promising approach to immune correction for the treatment of immune deficiency and autoimmune disorders. Recovery of the proliferative activity of the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…It is applicable in the prevention of oncological diseases and in the correction of the psychoemotional status of narcological patients [ 34 ]. Trecresan is also efficient in the complex treatment of tuberculosis and can be used in the case of heavy somatic pathology [ 41 ]. Trecresan can be used as an efficient drug in the complex system of the methods for the prevention and treatment of coronavirus infection aftereffects, including these related to bronchopulmonary pathology [ 42 ].…”
Section: Protatranesmentioning
confidence: 99%
“…It is applicable in the prevention of oncological diseases and in the correction of the psychoemotional status of narcological patients [ 34 ]. Trecresan is also efficient in the complex treatment of tuberculosis and can be used in the case of heavy somatic pathology [ 41 ]. Trecresan can be used as an efficient drug in the complex system of the methods for the prevention and treatment of coronavirus infection aftereffects, including these related to bronchopulmonary pathology [ 42 ].…”
Section: Protatranesmentioning
confidence: 99%
“…It is known that salicylic acid is widely used in cosmetology and medicine due to its antiseptic action. Based on the papers [14][15][16][17][18], it can be expected that triethanolammonium salicylate would have a similar effect. We …”
Section: The Influence On Growth Properties Of the Fungus Rhizopus Ormentioning
confidence: 99%
“…A number of studies have shown [14][15][16][17][18] that many protatranes have biological activity, which is mainly determined by the atrane structure of the cation and the nature of an anion. The first compound of this class was triethanolammonium salt of 2-methylphenyloxyacetic acid [2-CH 3 C 6 H 4 OCH 2 COO] -[NH(CH 2 CH 2 OH) 3 ] + (trecrezan), which is a drug of wide spectrum of action (adaptogen, immunomodulator, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crezoxyzincatran is an analogue of Tris 2(hydroxyethyl)ammonium 2 methylphenoxyacetate, an adaptogen and immunomodulator trecrezan. Trec rezan, similarly to many triethanolammonium salts of aroxyacetic acids, reduces the injury of elastic fibers, stabilizes cell membranes, and has a good biocompat ibility [5][6][7]. The detection of activation of TrpRS will make it possible to elucidate the molecular mecha nisms of action of CZA on the expression of TrpRS at various levels, including at the level of mRNA.…”
mentioning
confidence: 99%